Socio-Cultural Dimension of Epidemia of Syfilise in Eastern Galicia at the Time XIX/XX Century. On the Example of the Hutsul Region - Jakimowicz, Marcelina (Sensus Historiae, 2019)
In the researchers and writers narratives of the nineteenth-century population of Hutsul villages was portrayed as: innocent, plainly, free, honorable, but also: naive, brutal, wild and promiscuous. Hutsuls treated like a wild children, who need to be protected. In the 19th century an extremely problematic issue for Hutsuls’health was syphilis, which in this area evolved to epidemic disease. Despite the idealization of the character of the Hutsuls, researchers and writers describe the bad health condition and poor hygiene in the Hutsul villages. Article shows the problem the struggle of doctors about the health of mountaineers and attempts at treatment. The text also presents methods of the Hutsuls themselves of combating diseases, as well as the customs of Hutsul culture, including sexual freedom.